Quantifying ubiquitin dynamics - Bollinger, Sarah A., author; Cohen, Robert E., advisor; Peersen, Olve, committee member; Yao, Tingting, committee member; Prenni, Jessica, committee member; Alan, Kennan, committee member (Colorado State University. Libraries, 2019)
Ubiquitin (Ub) is a small protein that is frequently attached to other proteins as a post-translational modification (PTM) to elicit a new function, cellular localization, or otherwise modulate the activity of the substrate protein. Ub addition and removal serves as a signal for proteasome degradation, regulation of cell division, gene expression, membrane and protein trafficking and signaling in a multitude of stress response mechanisms. Defects in ubiquitination or deubiquitination have been linked to cancer onset and progression, muscle dystrophies, and disorders in inflammation and immunity; these findings further highlight the critical processes regulated by Ub. Due to its high demand, cellular Ub levels are highly regulated, such that the abundance of free Ub is above a threshold enabling new ubiquitination events, a critical part of normal cell function and survival. Due to the high demand on the cellular free Ub pool to supply substrate for thousands of ubiquitination reactions, it is tightly regulated in many ways. Our knowledge of Ub homeostasis has not advanced, likely due to the lack of accurate, sensitive methods for pool quantitation that can be performed routinely. Here, a method is presented that utilizes a high affinity free Ub binding protein to quantify cellular pools of Ub after a series of treatment protocols. The methods can be performed within a day and are amenable to high throughput applications. Using these methods, the Ub pool distributions of cells under conditions such as proteasome inhibitor and heat stress were assessed. However, this assay will only report the steady-state concentration of Ub in each pool; it provides no information about the rate of movement through them. The rates of competing ubiquitination and deubiquitination or degradation reactions determine the steady-state level of every Ub-protein conjugate; however, measurement of the rate of Ub movement these conjugates remains a challenge. Thus, the relative contributions of conjugation and disassembly rates in cellular responses to different signals are rarely known. Moreover, even though the concentration of a particular Ub-protein conjugate may appear unchanged, the flux of Ub through that conjugate might change dramatically. To address these deficits in our understanding of ubiquitination, we have developed a method to label Ub and follow its movement through conjugation pathways that we call SILOW or Stable Isotope Labeling with ¹⁸O-Water. Our method is applicable to both yeast and mammalian cells, does not perturb cellular physiology in any way and can be used with conventional proteomics methods. SILOW permits rapid changes in Ub flux to be evaluated over short times across hundreds of sites within the human cell proteome to reveal the intracellular dynamics of Ub-conjugation in specific Ub-Ub linkages of polyUb compared with Ub-protein linkages of histones.
Keywords: deubiquitination; flux; ubiquitination; dynamics; 18O; ubiquitin